Some Results of Feebly Open and Feebly Closed Mappings (Baghdad Science Journal, 2025)
The main purpose of this paper is to study feebly open and feebly closed mappings and we proved several results about that by using some concepts of topological feebly open and feebly closed sets , semi open (- closed ) set , gs-(sg-) closed set and composition of mappings.